Urban Cemeteries as Biodiversity Refuges: A Comparative Study of Plant Ecobiomorphs in Central Kazakhstan - Yelena Pozdnyakova; Aigul Murzatayeva (Diversity)
Cemeteries are often overlooked in ecological studies, yet they represent unique urban microhabitats that contribute to the preservation of diverse plant species, including those adapted to various ecological niches. This study aimed to assess the species composition, ecological classifications, and abundance of vascular plants in the cemetery and surrounding areas to explore cemeteries’ role in conserving plant ecobiomorph diversity in arid climates. This study identified 79 plant species from 23 families within the cemetery compared with 31 species from 11 families in the surrounding area. The plant community in the cemetery was dominated by mesophytes, suggesting favorable and stable conditions for plant growth, while xerophytes were more common in the surrounding areas, indicating harsher, drier conditions. The diversity of plant life forms, including perennial herbs, shrubs, and trees, was significantly higher within the cemetery, indicating a more complex and resilient ecosystem. Our study demonstrates that cemeteries act as vital refuges for plant biodiversity. They offer significantly higher species diversity and more complex ecosystem structures compared with the surrounding areas. These findings emphasize the critical role cemeteries play in urban biodiversity conservation, particularly in increasingly arid environments.